Mushrooms in climate change mitigation: a comprehensive review - Karunarathna, Samantha C.; Tibpromma, Saowaluck; Karunarathna, Baggya Sharmali; Dai, Dong-Qin; Kumla, Jaturong; Lu, Wenhua; Perera, Rekhani Hansika; Wang, Meimei; Priyadarshani, Tikka Dewage Chamarika; Hapuarachchi, Kalani Kanchana; Suwannarach, Nakarin (Frontiers in Microbiology, 2026)
Mushroom-forming basidiomycetes are increasingly recognized for their significant potential to remediate polluted environments and mitigate climate change. This review synthesizes evidence positioning mushroom-forming basidiomycetes at the nexus of ecological resilience and a sustainable bioeconomy, highlighting their dual roles in environmental repair and green innovation. Ectomycorrhizal (ECM species) enhance carbon acquisition by plants and long-term soil carbon sequestration; ECM-dominant forests stockpile upto 70% more below-ground carbon than their non-mycorrhizal counterparts. Saprotrophic fungi drive lignocellulose degradation, nutrient cycling, and the stabilization of soil organic matter. Basidiomycetes also play a crucial role in mycoremediation by degrading recalcitrant contaminants (pesticides, hydrocarbons) and immobilizing heavy metals. Furthermore, mycelium-based biomaterials are being developed as green-technology alternatives to plastics and synthetic foams, reflecting the growing commercialization of fungal biotechnology, as evidenced by the global mycelium material industry projected to exceed USD 5 billion by 2032. The intersection of ecological function and economic value positions mushrooms at the forefront of the circular bioeconomy. However, challenges remain, including production scalability, environmental sensitivity, and economic viability. Addressing these challenges through interdisciplinary research could unlock the full potential of fungi as nature-based climate solutions.